Estimation with mean square error for real-valued channel quantization - Trinca, Cibele Cristina; Belfiore, Jean-Claude; De Carvalho, Edson D. [UNESP]; Filho, Jozue Vieira [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Interference is usually viewed as an obstacle to communication in wireless networks, so we develop a new methodology to quantize real-valued channels in order to realize interference alignment onto a lattice. One key step is the introduction of an error criterion that measures, in a probabilistic sense, the error between the desired quantity and our estimate of it. So, in this work, we focus on choosing our estimate to minimize the expected or mean value of the square of the error, referred to as a minimum mean-square-error (MMSE) criterion.